The Role of Regular Tax Functions in the Pandemic Period Covid-19 at Pekanbaru - Wijoyo, Hadion; Devi, Wiara Sanchia Grafita Ryana; Ariyanto, Aris; Sunarsi, Denok (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
In addition to the budget function, tax also has a regular function which aims to regulate the economy of the Tax Tax (WP) so that there is a balance in tax imposition. This role was felt very strongly during the Covid-19 Pandemic where the economy became sluggish due to the decline in people's purchasing power. This study is to determine the direct effect of this function on the community structure in Pekanbaru. This study uses a qualitative method by taking samples, namely the SMEs actors. The results of this study are to determine the direct effect of tax stimulation on the sustainability of their businesses during the pandemic